Bangladeshi immigrants’ self-organization and associationism in Venice (Italy) - Mantovan, Claudia (Migration Letters, 2021)
In Italy, most of the studies on immigrants’ associationism and participation have concentrated on the more formal and structured aspects. Little research has been done on forms of immigrant self-organization not oriented towards the society in the country of adoption. Drawing on these considerations, this article analyzes the self-organization of Bangladeshi residents in the municipality of Venice considering both their infra-political and their politico-organizational mobilization, seeking relationships between these two spheres of action, identifying transnational bonds, and dynamics linked to the social and political context of their home country. At the same time, the study considers the influence of other factors, such as the social, political and economic context found in the country of immigration (at both national and local level), and also the personal variables that can influence people’s participation, such as gender, generation, social class, amount of time spent in the adopted country, legal status, formal education, human capital, attitudes and personal projects in general.